Paracoccidioidomycosis: clinical and epidemiological profile of hospitalized patients in Passo Fundo - RS - Franz, Ana Paula Giolo; Silva , Ana Flávia Missio da; Albuquerque, Antônio Benincá; Rovani , André Luca Boeira; Bonacina , Patrick; Barbosa , Gilberto da Luz; Scortegagna, Gabriela Trentin; Tonial, Fabiana (Revista de Medicina, 2022)
Paracoccidioidomycosis (PCM) is not a notifiable disease despite its relevance in Latin America, and therefore estimates of the prevalence, incidence, and associated morbidity of this mycosis are based on reports of epidemiological surveys, case series, hospitalization records, and mortality data. The objective of this study was to describe aspects related to the patient, disease evolution, diagnostic confirmation, and treatment of confirmed cases of PCM treated at a teaching hospital in southern Brazil. Information was collected from the medical records of 27 patients diagnosed with PCM, confirmed in the period from 2010 to 2019. The prevalent profile was a male patient, with a mean age of 53 years, who was involved in various work activities, of urban origin, immunocompetent and without comorbidities, and a smoker, but not an alcoholic. For most cases, the initial involvement was pulmonary, with significant involvement of the lymphatic system during the course of the disease. Microscopic observation of pathognomonic fungal structures in biopsy samples, lymph node aspirates, and sputum was the most common method to confirm the clinical suspicion. Itraconazole was the first treatment option, followed by amphotericin B.